THE DEVELOPMENT OF THE LEARNING MODEL FOR TEMPLES AND COMMUNITIES AROUND KHON KAEN’S KAEN NAKHON LAKE, KHON KAEN PROVINCE - Thongde, Vittaya; Promgun, Suraphon; Sawatta, Sutipong; Thabphumee, Phanthiwa (Journal of MCU Nakhondhat, 2025)
This research aimed to study the learning model of temples and communities in public spaces, to develop the learning process of temples and communities in public spaces, and to establish a learning network of temples and communities in public spaces around Bueng Kaen Nakhon, Khon Kaen Province. It was action research consisting of three sub-projects. The target groups were five temples and seven communities around Bueng Kaen Nakhon. Research tools included in-depth interviews, questionnaires, and participatory activities. Data were analyzed using descriptive content analysis. The results revealed that the temples and communities around Bueng Kaen Nakhon serve as important religious and cultural centers in terms of community building and identity, as follows: 1) The learning model of temples and communities in public spaces around Bueng Kaen Nakhon, Khon Kaen Province consists of core components that enhance and support effective and sustainable learning within the community context, including: 1.1) Using temples as centers for learning and cultural preservation, 1.2) Transferring knowledge through elders and monks, 1.3) Organizing local traditions and cultural arts activities, 1.4) Creating media and historical-cultural information resources, 1.5) Promoting participatory community learning, 1.6) Utilizing technology to expand learning, and 1.7) Evaluating and improving learning; 2) The development of learning among temples and communities in public spaces around Bueng Kaen Nakhon, Khon Kaen Province involves three stages: 2.1) Network search, 2.2) Brainstorming and designing, and 2.3) Developing learning activities in public spaces; 3) The establishment of learning networks of temples and communities in public spaces around Bueng Kaen Nakhon, Khon Kaen Province consists of 3.1) Planning, 3.2) Implementation, 3.3) Evaluation, and 3.4) Dissemination.